PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA SMK NEGERI 3 BANGLI - I Wayan Juniartawan; I Wayan Sujana; Ni Nyoman Ari Novarini (Forum Manajemen, 2020)
The progress of an institution is very much determined by the quality of the human resources in it. Humans are the most important resource in an organization in achieving success. All procedures and systems that are owned by an organization will be able to run if the HR is competent. The phenomenon that often occurs is the delay of employees in carrying out their duties. The purpose of this study was to obtain empirical evidence of the Effect of Democratic Leadership and Communication Style on Employee Performance at SMK Negeri 3 Bangli. The population in this study were 31 employees which is a total sampling. Research data collection was carried out by observation and questionnaire distribution. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis and hypothesis testing Democratic Leadership Style has a positive and significant effect on Employee Performance in State Vocational School 3 Bangli, Communication has a positive and significant effect on Employee Performance in State Vocational School 3 Bangli.